KAJIAN PERENDAMAN BENIH DAN MACAM PUPUK DAUN TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI (Glycine Max. L. Merril). - Ana Amiroh (Agriculture faculty, Darul ‘Ulum Islamic University (UNISDA) of Lamongan, 2017)
The efforts increased crop productivity requires the support of genetically superior seed supply, physical, and physiological as well as have a high power of adaptation to the environment grows. Low crop productivity caused by poor quality seeds used and the power of adaptation at low lingkunganyang especially in suboptimal environmental conditions. Efforts to enhance an already germinated the seeds of decline can be done by soaking the seeds in water (hydropriming) and various salt solutions (Osmoconditioning) as well as using organic material solids (Mafriconditioning). This research was carried out in the village of Sambigalih Sub-district Karang Sugio lamongan. This study used a Randomized Design Group (RAK) factorial pattern to two factors, namely: the fertilizer assortment of leaves (P) and soaking the seeds (L). Leaf fertilizer concentration factor consists of 3 levels namely: Regina Gandapan Leaf Fertilizer (P1), fertilizer Fertisim (P2), fertilizer Leaves Gandasil B (P3). Soaking the seed factor consists of three levels, namely: Water Solution (L1), solution of PGPR (L2) and solution of ZPT (L3). The best combination i.e. soaking of seed treatment with a solution of pgpr and regina gandapan leaf fertilizers (P1L2).